Rutting characteristics rolling-compacted open-graded friction courses - Phone Myint. (2008)
The goal of this research is to investigate the rutting behaviour and air voids of Land Transport Authority (LTA) Open-graded D2 gradation and a new gradation, which is recommended by the National Centre for Asphalt Technology, batched with conventional bitumen (PEN 60/70) and Cariphalte (PMB). Marshall stability and resilient modulus were used to evaluate their performances. Gyratory- compacted specimens were prepared by Gyratory Compactor, while two rut slabs (with 5 percent of optimum binder) were fabricated by Rolling Wheel Compactor.